Legal Anthropological Review of the Civil Registration Recognition following Tebo Regent Decrees Number 330 and 331 of 2021: (A Case Study of the Suku Anak Dalam Community in Sungai Abang) - Abdurrahman, Syarif; Ulfa Uluwiyah, Dewi (Department of Constitutional Law, Faculty Sharia and Law, UIN Sunan Ampel Surabaya, 2024)
This study examines the recognition of the civil registration status of the Indigenous Law Community of the Suku Anak Dalam (SAD) in Sungai Abang, Tebo Regency, Jambi Province, from a legal-anthropological perspective. The primary issue addressed is how the local government has implemented civil registration recognition through Regent Decrees Number 330 and Number 331 of 2021, concerning the recognition of the Indigenous Law Community of the Suku Anak Dalam in Muara Kilis and Tanah Garo. This research employs a descriptive qualitative method, utilizing interviews, observation, and documentation as data collection techniques. The findings indicate that the Tebo Regency Government, during the administration of Regent Sukandar, formally recognized indigenous law communities as entities entitled to legal protection. However, no formal recognition has yet been granted to the SAD community of Sungai Abang. Consequently, the Sungai Abang SAD community continues to face difficulties in obtaining civil registration documents, such as identity cards, and in accessing public services, including healthcare.